Immunization goals: Is Nepal keeping the promises? - Suvedi, B.K. (Journal of Institute of Medicine Nepal, 2007)
Nepal committed to the global immunization goals in 1992 as expressed in the World Health Assembly of 1989. This article examines whether Nepal has attempted to keep the promises. It is seen that the promises are being seriously taken and fulfilled as evidenced by various activities carried out in the past one decade. Journal of Institute of Medicine Vol.27(3) 2005